Numerical models for simulation of the seismic behaviour of RC structures: a case study - Varum, H. (2007)
Seismic analysis of RC structures requires realistic but simple analytical models. In this paper are presented two models proposed and implemented in the program PORANL, to represent the RC buildings behaviour under earthquake loading. The first model represents the bending behaviour of slender RC elements, and the second model represents the influence of infill walls in the global building response. The models are calibrated with test results on full-scale specimens. It is studied the vulnerability of one building, representative of the Modern Architecture, in Lisbon. Non-destructive tests on materials and natural frequencies measurement were performed to calibrate the model. The building was studied, with the proposed non-linear models, and the seismic safety was evaluated according to recently proposed assessment procedures. Additionally, it is proposed and studied a retrofitting solution, to improve the seismic performance of the building, based on a bracing system with a damping device associated.